DESIGN AND CONSTRUCTION OF A DIFFERENTIAL AMPLIFIER CIRCUIT FOR EDUCATIONAL PURPOSES - Stein, Edmilton Oliveira; Rasia, Luis Antonio; Valdiero, Antonio Carlos; Dambroz, Giovani Prates Bisso; Alves, Mônica Raquel; Valdiero, Carlos Augusto (Salão do Conhecimento, 2018)
Research Project carried out at UNIJUÍ’s Mechanical Engineering Course